An adnexal mass at the cesarean section - Edral,Ana (2017)
Splenosis refers to the presence of ectopic splenic tissue through autotransplantation following traumatic rupture of the spleen or splenectomy. We report the case of a previously asymptomatic 31-year-old pregnant woman who had undergone splenectomy at 12 years of age after traumatic splenic rupture. She was submitted to cesarean section, during which multiple bluish-red nodules were found on the greater omentum and a bigger one adjacent to the right ovary as an incidental finding. Histopathology revealed the presence of supernumerary splenic tissue. We aim to raise awareness to this diagnosis since this benign finding can mimic several gynecological diseases.